^{2}and 5x, then we get the result 4x

^{2}+ 5x.

On another hand if we have to add two terms 5x

^{3}and (- 3x

^{3}). So we observe that two terms are like and we get the result as: 5x

^{3}+ (- 3x

^{3}) = 2x

^{3}.

In same way we say that subtraction of two monomials can also be done. For this we will proceed in following way: Subtract 3x

^{2}from - 8x

^{2}. So we will write above statement as follows: - 8x

^{2}– 3x

^{2}= - 11x

^{2}.

On other hand if two terms are unlike terms, we will simply write two terms as the difference and the coefficient of two terms that are not actually subtracted in such cases. Example: Subtract 3x from 6y can be written as 6y – 3x.

Now we will look at how to find the product of the two monomials say 2x and 5y. Here the numerical coefficient of two terms is multiplied and variables are multiplied. Thus we will get 2x * 5y = (2 * 5) * x * y.

= 10xy

Also we get 2x

^{2}* 4x

^{2}= (2 * 4) x2 * x

^{2}= 8 x (2 + 2),

= 8 x 4.